PENGEMBANGAN LKS BERBASIS CONTEXTUAL TEACHING AND LEARNING PADA PEMBELAJARAN IPA MATERI DAUR AIR KELAS V SD NEGERI 101797 DELI TUA - Maisaroh; Samsul Bahri (PENDALAS: Jurnal Penelitian Tindakan Kelas dan Pengabdian Masyarakat, 2021)
This research is based on the problems found in SD Negeri 101797 Deli Tua, namely the science learning outcomes that are still low at the elementary school. This is evidenced by the discovery of several problems, namely learning activities for science subjects lack of direct observation and experiments on the material being taught so that students are impressed only by listening to the teacher's explanations and memorizing textbooks, Student Worksheets (LKS) used are fixated on the subject matter. material texts and questions, and lack of developing student activities that are directly related to the student environment. From the problems developed by the CTL-based LKS, it aims to (1) create CTL-based LKS in the science learning of water cycle materials for class V elementary school, (2) to determine the feasibility of CTL-based LKS in learning science for class V elementary school water cycle materials. This type of research is Research and Development (R&D) using the Borg and Gall model modified by Sugiyono with 10 stages but the researcher only uses 5 stages. The stages in research and development are Potential and Problems, Data Collection, Product Design, Design Validation, and Design Revision. The product validation stage was validated by 2 validators, namely 1 media expert and 1 class V teacher. The validation results on the Contextual Teaching And Learning-based LKS by media experts obtained a score of 3.97 with a good category, and the validation results by class V teachers obtained a score of 4.27 with very good category. And obtained the average score of the two hali 4.12 in the good category. It was concluded that the LKS based on contextual teaching and learning in science learning for class V water cycle materials at SD Negeri 101797 Deli Tua was developed to be suitable for use as teaching materials.